The investigation of the dynamic behaviour of a complex structure using the wave-based substructuring method / Ahmad Burhani Ahmad Basri - Ahmad Basri, Ahmad Burhani (2009)
Analysing the dynamic properties of a complex structure with a large number of substructures frequently leads the modal analysts to carefully select the appropriate methods for the optimal balance between the economics and accuracy of the analysis.